Alteration in cytochrome P450 3A4 activity as measured by a urine cortisol assay in HIV‐1‐infected pregnant women and relationship to antiretroviral pharmacokinetics. Issue 3 (18th November 2014) - Aweeka, FT; Hu, C; Huang, L; Best, BM; Stek, A; Lizak, P; Burchett, SK; Read, JS; Watts, H; Mirochnick, M; Capparelli, EV; the International Maternal Pediatric Adolescent AIDS Clinical Trials Group (IMPAACT) P1026s Protocol Team
<x xml:space="preserve">Abstract</x> Objectives Pregnancy results in physiological changes altering the pharmacokinetics of drugs metabolized by cytochrome P450 3A4 (CYP3A4). The urinary ratio of 6‐β hydroxycortisol to cortisol (6βHF : F) is a marker of CYP3A4 induction. We sought to evaluate its change in antiretroviral (ARV)‐treated HIV‐1‐infected women and to relate this change to ARV pharmacokinetics. Methods Women receiving various ARVs had pharmacokinetic evaluations during the third trimester of pregnancy (> 30 weeks) and postpartum with determination of 6βHF : F carried out on the same days. The Wilcoxon signed rank test was used to compare the ratio antepartum to postpartum. The relationship between the change in ratio and the change in pharmacokinetics was analysed using Kendall's tau. Results 6βHF : F ratios were available for 107 women antepartum, with 54 having postpartum values. The ratio was higher antepartum (P = 0.033) (median comparison 1.35; 95% confidence interval 1.01, 1.81). For 71 women taking a protease inhibitor (PI), the antepartum vs. postpartum 6βHF : F comparison was marginally significant (P = 0.058). When the change in the 6βHF : F ratio was related to the change in the dose‐adjusted ARV area under the plasma concentration vs. time curve (AUC) between antepartum and postpartum, the 35 subjects in the lopinavir/ritonavir (LPV/r) arms demonstrated an inverse relationship (P = 0.125), albeit this correlation did not reach statistical significance. Conclusions A 35% increase in the urinary 6βHF : F ratio was measured during late pregnancy compared with postpartum, indicating that CYP3A induction occurs during pregnancy. The trend towards an inverse relationship between the change in the 6βHF : F ratio and the change in the LPV AUC antepartum vs. postpartum suggests that CYP3A induction may be one mechanism behind altered LPV exposure during pregnancy.